Public confidence in criminal justice in Canada: A comparative and contextual analysis - Roberts, J (2007)
Public confidence in criminal justice has emerged as an important issue in most western nations. Several jurisdictions have made promoting public confidence a policy priority, and governments in many countries have recently conducted public opinion surveys to gauge levels of confidence in criminal justice. However, little is known about levels of public confidence in criminal justice in Canada. This article reviews the empirical research on this issue and attempts to explain current trends. Although a significant plurality of the public expresses little confidence in the justice system, more people are positive than are negative. In comparison to other countries, confidence levels in criminal justice are generally higher in Canada. This said, the public has less confidence in the justice system than in other public institutions such as the health care system. Consistent with findings elsewhere, the police attract most, and the prison system the least amount of public confidence. The article places these findings in context, and discusses their implications for research and policy. © 2007 CJCCJ/RCCJP.